Scientific Methods of Optimization of Labor Safety in Economic Sectors - Rakhmonberdievich, Yuldashev Orynbai; Razzokov, Khabib Kholikovich (European Journal of Life Safety and Stability (2660-9630), 2022)
The article describes in detail the optimization of the management system, providing on the basis of mathematical methods and information analysis, the adoption and implementation of management decisions on labor safety in economic sectors.